2018
DOI: 10.1002/anie.201806799
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative Negishi Coupling of Redox‐Active Aliphatic Esters by Cobalt Catalysis

Abstract: A cobalt-catalyzed decarboxylative Negishi coupling reaction of redox-active aliphatic esters with organozinc reagents was developed. The method enabled efficient alkyl-aryl, alkyl-alkenyl, and alkyl-alkynyl coupling reactions under mild reaction conditions with no external ligand or additive needed. The success of an in situ activation protocol and the facile synthesis of the drug molecule (±)-preclamol highlight the synthetic potential of this method. Mechanistic studies indicated that a radical mechanism is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 95 publications
0
47
0
Order By: Relevance
“…For this purpose, one feasible way is to activate the carboxylic acids and alkyl primary amines to the corresponding redox-active esters (RAE) and Katritzky's N-alkylpyridinium salts, respectively 16,17 . Previous studies demonstrated that both RAE [18][19][20][21][22][23][24][25][26][27][28] and Katritzky's salts [29][30][31][32][33][34][35][36][37] are predisposed to accept an electron from low-valent transition metals or organic Lewis bases under photocatalytic reaction conditions, thereby acting as precursors to the corresponding alkyl radicals (Fig. 1b) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] .…”
mentioning
confidence: 99%
“…For this purpose, one feasible way is to activate the carboxylic acids and alkyl primary amines to the corresponding redox-active esters (RAE) and Katritzky's N-alkylpyridinium salts, respectively 16,17 . Previous studies demonstrated that both RAE [18][19][20][21][22][23][24][25][26][27][28] and Katritzky's salts [29][30][31][32][33][34][35][36][37] are predisposed to accept an electron from low-valent transition metals or organic Lewis bases under photocatalytic reaction conditions, thereby acting as precursors to the corresponding alkyl radicals (Fig. 1b) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] .…”
mentioning
confidence: 99%
“…Furthermore, decarboxylative fragmentation of redox active esters (RAEs) enables the generation of alkyl radicals under photoredox conditions using Ir, Ru, and other photocatalysts . Meanwhile, transition metals such as Ni, Fe, Cu, Co, Cr, and other metal species have also been used to reduce RAEs via thermal single‐electron transfer (SET) to form alkyl radicals. Through similar mechanisms, oxalate derivatives can produce tertiary radicals through Ir‐, Ru‐catalyzed photoredox conditions or Zn metal and Ni with ligands .…”
Section: Figurementioning
confidence: 99%
“…quaternary stereogenic centers. Furthermore, the NHPIbased redox-active esters can also accept electrons from simple metal catalysts, such as cobalt, 41 copper, 42,43 iron, 44 and nickel, [45][46][47][48][49][50] through thermal SET events. 51,52 Inspired by the work of the Okada and Oda group, in 2016 the König group reported a metal-free method for the decarboxylative alkylation of biomass-derived carboxylic acids (Scheme 2).…”
Section: Syn Thesismentioning
confidence: 99%